2023
DOI: 10.1159/000530624
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptome Sequencing Reveals Molecular Mechanisms of Renal Injury in Essential Hypertension

Abstract: Introduction: Hypertensive nephropathy is characterized by glomerular and tubulointerstitial damage, but we know little about changes in cell-specific gene expression in the early stages of hypertensive kidney injury, which usually has no obvious pathological changes. Methods: We performed unbiased single-cell RNA sequencing of rat kidney samples from hypertensive kidney injury to generate 10602 single-cell transcriptomes from 2 control and 2 early stage of hypertensive kidney injury samples. Results: All majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Inflammation is believed to play a pivotal role in the intricate relationship between hypertension, diet, and renal health. Animal studies have demonstrated that hypertension can induce glomerular injury by compromising the integrity of the glomerular capillaries and exacerbating local renal inflammation [ 55 ]. The tissue damage triggered by hypertension can stimulate the generation or presentation of antigens, leading to an immune response and stimulates the release of inflammatory mediators [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is believed to play a pivotal role in the intricate relationship between hypertension, diet, and renal health. Animal studies have demonstrated that hypertension can induce glomerular injury by compromising the integrity of the glomerular capillaries and exacerbating local renal inflammation [ 55 ]. The tissue damage triggered by hypertension can stimulate the generation or presentation of antigens, leading to an immune response and stimulates the release of inflammatory mediators [ 53 ].…”
Section: Discussionmentioning
confidence: 99%